LITERASI DIGITAL TENTANG VAKSIN COVID-19 DI KALANGAN GURU SMA DI INDONESIA - Xenia Angelica Wijayanto; Lamria Raya Fitriyani; Lestari Nurhajati (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2022)
Various statements about Covid-19 vaccines from the government became a lot of discussion, including among teachers. Government public communication should be carried out to manage diverse polemics and public opinion. Discussions about the planning and process of vaccine administration come with different approaches, thinking skills and knowledge, especially with the increasing use of communication technology such as internet and social media. This difference in knowledge and perception can be bridged if there are parties who help socialize the benefits and importance of the COVID-19 vaccine, such as teacher, one of the gate keepers in selecting information and public dissemination. The specific purpose of this research is to get a complete picture of how digital literacy skills and teachers' perceptions of information regarding the delivery of the Covid-19 vaccine. Method used are by distributing online questionnaires to high school teachers in Indonesia (DKI Jakarta, Yogyakarta, Bali, South Kalimantan and South Sulawesi) with approximately 493 samples. From the discussion, SMA/SMK teachers in Indonesia have excellent digital literacy skills related to COVID-19 Vaccine information in online media. It's just that unfortunately the ability to produce, modify and participate in organizations that produce messages related to COVID-19 Vaccine information is still relatively low.